Inotuzumab ozogamicin: a CD22 mAb–drug conjugate for adult relapsed or refractory B-cell precursor acute lymphoblastic leukemia - Yurkiewicz IR; Muffly L; Liedtke M (Dove Medical Press, 2018)
Ilana R Yurkiewicz,1 Lori Muffly,2 Michaela Liedtke1 1Department of Medicine, Division of Hematology, Stanford University School of Medicine, Stanford, CA, USA; 2Department of Medicine, Division of Blood and Marrow Transplantation, Stanford University School of Medicine, Stanford, CA, USA Abstract: Despite improved rates of remission and cure in newly diagnosed adult acute lymphoblastic leukemia (ALL), the prognosis for patients with relapsed or refractory disease remains poor and the 5-year overall survival rate after relapse is under 10%. A recent paradigm shift has focused on the promise of targeted immunotherapy rather than standard chemotherapy, as ALL blast cells express a variety of antigens, and monoclonal antibodies may be developed to identify and destroy the leukemic cells. Inotuzumab ozogamicin is a CD22 monoclonal antibody conjugated to the cytotoxic antibiotic calicheamicin. CD22 expression is detected on leukemic blasts in over 90% of patients with ALL. Based on promising results from preclinical studies, inotuzumab ozogamicin was tested in Phase 1/2 and Phase 3 clinical trials and it demonstrated improved complete remission rates, progression-free survival and overall survival in relapsed or refractory adult ALL compared to standard therapy. Ongoing studies are evaluating the value of inotuzumab ozogamicin when given in combination with chemotherapy as part of upfront treatment. This review discusses the drug’s biochemical properties and mechanism of action, preclinical research outcomes, clinical trial results, adverse events and toxicities, drug approval and ongoing investigations. Keywords: acute lymphoblastic leukemia, relapsed/refractory, inotuzumab ozogamicin, monoclonal antibody–drug conjugate, CD22